2016
DOI: 10.3945/ajcn.116.130518
|View full text |Cite
|
Sign up to set email alerts
|

Mortality in children with complicated severe acute malnutrition is related to intestinal and systemic inflammation: an observational cohort study

Abstract: Background: Diarrhea affects a large proportion of children with severe acute malnutrition (SAM). However, its etiology and clinical consequences remain unclear.Objective: We investigated diarrhea, enteropathogens, and systemic and intestinal inflammation for their interrelation and their associations with mortality in children with SAM.Design: Intestinal pathogens (n = 15), cytokines (n = 29), fecal calprotectin, and the short-chain fatty acids (SCFAs) butyrate and propionate were determined in children aged … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
154
2
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 125 publications
(167 citation statements)
references
References 40 publications
10
154
2
1
Order By: Relevance
“…Two studies among children with SAM, using PCR, reported a prevalence of Giardia of 33% and 38%, respectively [14,15], which is in line with our findings. The lack of association between Giardia and diarrhoea in our study might be due to lack of power, but our finding is in line with several studies, some of which reported higher detection rates of Giardia among non-diarrhoeal controls than among children with diarrhoea [16,30].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Two studies among children with SAM, using PCR, reported a prevalence of Giardia of 33% and 38%, respectively [14,15], which is in line with our findings. The lack of association between Giardia and diarrhoea in our study might be due to lack of power, but our finding is in line with several studies, some of which reported higher detection rates of Giardia among non-diarrhoeal controls than among children with diarrhoea [16,30].…”
Section: Discussionsupporting
confidence: 92%
“…The lack of association between Giardia and diarrhoea in our study might be due to lack of power, but our finding is in line with several studies, some of which reported higher detection rates of Giardia among non-diarrhoeal controls than among children with diarrhoea [16,30]. Previous studies also failed to find an association between G. duodenalis and clinical outcome among children with SAM [14,15]. This questions the relevance of diagnosing children with SAM for G. duodenalis.…”
Section: Discussionsupporting
confidence: 78%
“…In severe malnutrition, the lack of antioxidants and nutrients necessary for endogenous antioxidants and a major liver peroxisomal and mitochondrial dysfunction results in a major oxidative stress [10][11][12] . In children with severe acute malnutrition, we have shown a major depletion of anaerobic microbes (or intolerant to reactive oxidative species) 12 , consistent with the collapse of fecal butyrate in those who die 13 . This led us to found that antioxidants allow most anaerobes, including methanogenic archaea, to thrive in an oxidative environment (aerobic) [14][15][16] .…”
Section: Introductionsupporting
confidence: 61%
“…Retarded growth is a condition that directly affects morbidity and mortality in childhood (8,9). According to World Health Organization data, pneumonia, diarrhea, malaria, measles and AIDs represent the cause of death in more than half of children under 5, and inadequate nutrition is present in one in three of these patients (10).…”
Section: Discussionmentioning
confidence: 99%